HUBUNGAN ANTARA SYNDROM FEAR OF MISSING OUT DENGAN SIKAP PERCAYA DIRI SISWA SMAN 3 PALU - Izzha, Nurul; Syahran, Ridwan; Munifah, Munifah; Silalahi, Micha Felayati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Finding out how students' levels of self-confidence relate to their FOMO (Fear of Missing Out) is the primary goal of this research. This study used two questionnaires to gather data: one measuring students' levels of self-confidence and the other measuring their fear of missing out. The data were used for both descriptive and inferential purposes, with a significance level of 95% and the product moment correlation formula. Descriptive analysis revealed the following percentages of students: 3.17% with extremely high FOMO, 59.79% with high FOMO, 36.51% with low FOMO, and 0.53% with extremely low FOMO. Additionally, 9.52% of students had extremely high self-confidence, 86.77% with high self-confidence, 3.70% with low self-confidence, and 0% with extremely low self-confidence. A coefficient value of -0.027 was also shown in the inferential test results. As the computed r value is higher than the r table value (-0.027 < 0.1428), it can be concluded that the Fear of Missing Out Syndrome variable does not correlate with students' self-confidence. ABSTRAKMencari tahu bagaimana tingkat kepercayaan diri siswa berhubungan dengan FOMO (Fear of Missing Out) mereka adalah tujuan utama dari riset ini. Riset ini menggunakan dua kuesioner untuk mengumpulkan data: satu mengukur tingkat kepercayaan diri siswa dan yang lainnya mengukur rasa takut mereka akan ketinggalan. Data digunakan untuk tujuan deskriptif dan inferensial, dengan tingkat signifikansi 95% dan rumus korelasi momen produk. Analisis deskriptif mengungkapkan persentase siswa berikut: 3,17% dengan FOMO yang sangat tinggi, 59,79% dengan FOMO tinggi, 36,51% dengan FOMO rendah, dan 0,53% dengan FOMO yang sangat rendah. Selain itu, 9,52% siswa memiliki kepercayaan diri yang sangat tinggi, 86,77% dengan kepercayaan diri yang tinggi, 3,70% dengan kepercayaan diri yang rendah, dan 0% dengan kepercayaan diri yang sangat rendah. Nilai koefisien -0,027 juga ditunjukkan dalam hasil uji inferensial. Karena nilai r hitung lebih besar dari nilai r tabel (-0,027 < 0,1428), maka dapat disimpulkan bahwa variabel Fear of Missing Out Syndrome tidak berkorelasi dengan kepercayaan diri siswa.